Essential Angular for ASP.NET Core MVC 3 : a practical guide to successfully using both in your projects - Freeman, Adam, 1972- (Apress, 2019)
Combine the strengths of Angular, the leading framework for developing complex client-side applications, and ASP.NET Core MVC 3, the latest evolution of Microsofts framework for server-side applications. This new edition offers updated Angular, ASP.NET Core 3, Entity Framework Core 3 examples, an all-new chapter on interoperability with Blazor, and more! Best-selling author Adam Freeman brings together these two key technologies and explains how to use ASP.NET Core MVC 3 to provide back-end services for Angular applications. This fast-paced and practical guide starts from the nuts and bolts and gives you the knowledge you need to combine Angular and ASP.NET Core MVC 3 in your projects. Each topic is covered clearly and concisely and is packed with the essential details you need to learn to be truly effective. What You Will Learn Gain a solid understanding of how ASP.NET Core MVC 3 and Angular can work together Utilize both Visual Studio and Visual Studio Code to develop Angular/ASP.NET Core MVC projects Create ASP.NET Core RESTful web services to support Angular applications Expose data from Entity Framework Core to Angular applications Use ASP.NET Core Identity to provide security services to Angular applications Understand how Angular and Blazor applications can work together.